Galtier, Pasteur e Roux: estudos sobre a raiva (1879 1885) - Rodrigues, Sabrina Páscoli (2010)
Nowadays, in general, the chemist Louis Pasteur (1822-1895) takes all the credit for the researches that led to the production of the vaccine against hydrophobia. This dissertation deals with Pasteur s contributions concerning this subject, from 1879 to1885, taking into account its context. It also discusses the contributions from the veterinary Pierre Victor Galtier (1846-1908) and the physician Émile Roux (1853-1933). The aim of this research is trying to elucidate the existence of a possible superiority or priority concerning some important contributions related to rabies considering Pasteur, Galtier and Roux s publications on the subject during the period. This dissertation contains an introduction and four chapters. Chapter 1 provides an overview of Pasteur s researches before carrying out his researches on rabies, as well as its scientific context. Chapter 2 discusses the researches on rabies did by Galtier (1846-1908). Chapter 3 analyses the researches on rabies conducted by Pasteur and his collaborator, Roux. Chapter 4 presents some final remarks on the subject. This study led to the conclusion that the vaccine against rabies is the product of several scientists work such as Galtier, Roux and Pasteur. Besides that, it pointed out that Pasteur s contribution on the subject was not so significant as it is normally thought. Galtier and Roux should have achieved recognition indeed. Moreover, the popular version of this episode cannot be explained only taking into account Pasteur s scientific contributions on the subject